Improvisation and university students’ entrepreneurial intention in China: The roles of entrepreneurial self-efficacy and entrepreneurial policy support - Guo, Runping; Yin, Haobo; Lv, Xingqun (Frontiers in Psychology, 2022)
In the VUCA era, determining how to deal with environmental uncertainty has become one of the core issues. Research shows that improvisation is an effective way to deal with rapid changes and to obtain unexpected opportunities in a complex and changeable environment. Improvisation, as a needed capability in the entrepreneurial process, can also provide key strategies to effectively deal with emergencies. Although previous studies have explored the outcomes of improvisation in the entrepreneurial field, this paper aims to investigate in depth whether and how improvisation affects entrepreneurial intention in China. A moderated mediation model was constructed and tested using data from 251 Chinese university students to explore the influence mechanism of improvisation on entrepreneurial intention by combining social cognitive theory and the entrepreneurial event model. The results of this empirical analysis found that improvisation has a positive effect on entrepreneurial intention and entrepreneurial self-efficacy. Entrepreneurial self-efficacy plays a fully mediating role in the relationship between improvisation and entrepreneurial intention. Moreover, entrepreneurial policy support has been found to significantly moderate the mediated relationship between improvisation and entrepreneurial intention by entrepreneurial self-efficacy. The findings suggest that individuals should cultivate improvisation capabilities and entrepreneurial self-efficacy to enhance their entrepreneurial intention. They also need to pay attention to the dynamics of entrepreneurial policies in China. This study contributes to the extant literature by providing deeper insight into the relationship between improvisation and entrepreneurial intention and also has important practical implications for promoting entrepreneurial intention formation in contexts with environmental uncertainty like China.